Western Anatolia before Troy Proto-Urbanisation in the 4th Millenium BC? Proceedings of the International Symposium held at the Kunsthistorisces Museum Wien Vienna, Austria, 21-24 November, 2012 - Horejs, Barbara; Mehofer, Mathias (OREA (1), 2014)
OREA 1 presents the scientific results of the international symposium Western Anatolia before Troy - Proto-Urbanisation in the 4th Millennium BC? The sparse archaeological data published for the 5th and 4th millennia BC and the archaeological picture of western Anatolia, fundamentally changed in the last decades, needed to bring together specialists of western Turkey and the neighbouring regions to discuss new data in the light of socio-cultural processes in the period before Troy. Furthermore, following the results of the ERC research group (ERC project Prehistoric Anatolia), it appeared high time to focus on this period as it had been frequently neglected in the recent dynamic prehistoric research in western Turkey.